PENGARUH KUALITAS PRODUK, BRAND IMAGE, DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN DENGAN TRUST SEBAGAI VARIABEL MEDIASI: Studi Pada Pengguna Scarlett Whitening Body Lotion - Rosalina Pepin Nudya; Andjarwati, Anik Lestari (Universitas Negeri Surabaya, 2025)
During the COVID-19 pandemic, various local cosmetic brands experienced significant growth. One of the local cosmetic brands in the body care category is Scarlett Whitening Body Lotion. The increase in sales of Scarlett Whitening products has been very extreme. It has entered the ranks of top brands and can compete with other skincare brands, but it has not yet completely dominated the market. This research aims to determine the influence of product quality, brand image, and brand ambassador on purchasing decisions, with trust serving as a mediating variable. This research type is quantitative research. Respondents in this research were consumers aged 20 to 40 years who had purchased and used Scarlett Whitening body lotion products within the last 3 months and were familiar with actor Song Joong Ki as the Scarlett Whitening brand ambassador. The non-probability sampling technique employed is judgmental sampling, with a sample size of 220. Data processing utilises the path analysis technique. This research reveals a positive and significant relationship between product quality, brand image, and brand ambassador on purchasing decisions, with trust serving as a mediating variable for Scarlett Whitening body lotion users. Companies should enhance product quality, strengthen brand image, and strategically leverage trusted brand ambassadors to build consumer trust and drive purchasing decisions in the competitive body care market.